2021
DOI: 10.1097/mpg.0000000000003214
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Concentration in Human Milk in the First Ten Days Postpartum

Abstract: Background & objectives:Human milk (HM) is better tolerated than formula in preterm infants. Insulin, which is naturally present in HM but not in formula, has been suggested as a key factor for feeding tolerance, as it appears to stimulate intestinal maturation. Its precise concentrations during the early postnatal period, however, remains unknown. The objective of this study was to assess the natural timecourse of the HM insulin concentration during the first ten days postpartum. The effect of preterm deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The central-controlled computer program generated a randomization number and an investigational medical product (IMP) pack number for each infant. The dosage of 400 μIU/mL is comparable with the natural physiological peak insulin concentration in human colostrum, and the dosage of 2000 μIU/mL is supraphysiological relative to the natural insulin concentration in human colostrum …”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…The central-controlled computer program generated a randomization number and an investigational medical product (IMP) pack number for each infant. The dosage of 400 μIU/mL is comparable with the natural physiological peak insulin concentration in human colostrum, and the dosage of 2000 μIU/mL is supraphysiological relative to the natural insulin concentration in human colostrum …”
Section: Methodsmentioning
confidence: 94%
“…The intestinal stimulating effect of mother’s own milk appears attributed to its numerous nonnutritive bioactive factors, including the peptide hormone insulin . It has been shown that the natural insulin concentration in human milk peaks in the early postpartum period but declines to a basal level within the first 3 days post partum . To date, insulin is absent in formula.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the lower scores attained by women with no history of pregnancy (3.93 ± 2.50 point) or childbirth (3.76 ± 2.52 point) (Table 3) might be related to the younger age of this group and their relatively low exposure to women healthcare. [16] However, women at an early age, during the first pregnancy or delivery, or with more frequent pregnancies also had relatively low scores on cervical cancer awareness (Table 3), which might be related to the lack of attention to their health. [17,18] Therefore, besides strengthening awareness and education about cervical cancer for this population, it was necessary to focus on the overall health level.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, starting from a level of 8 μM/L insulin, a 2-fold dilution series was obtained until reaching an amount of 58.59 pM/L insulin and aliquoted in a 96-well microtiter plate. In addition, insulin at a physiologically relevant concentration of 157 pM/L was also included in the assay ( 51 ). Subsequently, an overnight culture of the above-mentioned bifidobacterial strains was diluted to obtain an optical density at 600 nm (OD 600nm ) of ~1, and 15 μL of the diluted cells were inoculated in 135 μL of MRS broth supplemented with a specific insulin amount.…”
Section: Methodsmentioning
confidence: 99%